مقومات نجاح المصارف الإسلامية في سورية "دراسة مقارنة بين المصارف الإسلامية والمصارف التقليدية" - نادر, نهاد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد المصارف عصب الاقتصاد ومحركه لأنها تحفظ الأموال وتحركها وتنميها وتسهل تداولها, ونظراً للدور الكبير الذي تقوم به تم ظهور مصارف لا تتعارض مع مبادئ الشريعة الإسلامية, وهي المصارف الإسلامية التي أصبحت ركيزة أساسية في السوق المالية العالمية والعربية. وفي بحثنا هذا سوف نستعرض نشأة ونمو المصارف الإسلامية عالمياً وعربياً ومحلياً, وأهدافها ومبررات وجودها وآلية عملها واختلافها مع المصارف التقليدية , مع إجراء مقارنة بين المصرف الدولي الإسلامي في سورية والمصرف التجاري السوري من حيث الأهداف, صيغ التمويل, المنافسة, الرقابة, تحمل المخاطرة, النظرة إلى المصرف على أنه تاجر أم وسيط مالي, كما سنناقش مقومات نجاح المصارف الإسلامية في سورية, مع توضيح مدى إقبال المواطنين السوريين على التعامل مع المصارف الإسلامية, ومدى توفر متطلبات نجاح هذه المصارف في سورية تمهيداً لاقتراح توصيات تساهم في توعية الأفراد لأهميتها والأهداف السامية التي تسعى إلى تحقيقها المصارف الإسلامية من جهة, ولضمان نجاح هذه المصارف في توظيف أموالها في القنوات الاستثمارية المناسبة من جهة أخرى. Banks are the backbone of economy because they keep money, circulate it, and facilitate exchange. Due to the great role of the banks, new kinds of banks that work according to Sharia (Islamic law) were opened. These are the Islamic banks which became one of the fundamentals in the Arabic and international Market. We will focus on the existence and growth of Islamic banks, internationally, in the Arabic region and locally. We will also focus on their objectives, explain their operation, then a comparison will be made between the International Islamic Bank in Syria and The Commercial Bank of Syria according to: objectives, financing methods, competition, control, risk takeover, the idea about the bank as a trader or broker, and identify the Syrians' interest in dealing with the Islamic banks and the availability of the factors of their success in Syria. This will help us put forward some recommendations that help enlighten the importance of the sublime objectives of the Islamic banks on the one hand, and to guarantee their success in investing their capital in the suitable channels of investments.